RE-OS FRACTIONATION IN ECLOGITES AND BLUESCHISTS AND THE IMPLICATIONS FOR RECYCLING OF OCEANIC CRUST INTO THE MANTLE - Becker H. (My University, 2000)
Metabasalts (eclogites, blueschists and mafic granulites) metamorphosed in paleosubduction zones show a range in rhenium (Re) abundances between 3 and 1689 parts per trillion (ppt), with a median value of 331 ppt Re. The median Re abundance of the metabasites corresponds to only ∼40% of the Re abundances expected for likely mafic protoliths. Osmium (Os) abundances in the metabasites (2–42 ppt, with one sample at 909 ppt) are comparable to abundances in mid-ocean ridge basalt (MORB). Re was lost from the protoliths either during dehydration, the most likely explanation, or during alteration of the protoliths near the ocean ridges. Radiogenic 187Os/188Os and 206Pb/204Pb of HIMU ocean island basalts (OIB) that are believed to contain a component of recycled altered MORB would require excessive amounts (>80–90%) of ∼0.5–1 Gyr old recycled altered MORB in the mantle source, if constraints on Re/Os and U/Pb from the metabasites are applied. The necessary amount of recycled component is only marginally lower (70%) if equal amounts of altered and unaltered 2 Gyr old MORB are present in the mantle source. Considering the major element abundances in alkaline OIB, these estimates appear unreasonably high. One possibility is that the simple bulk mixing models commonly employed are not applicable. Rapid melting during the formation of alkaline basalts and sluggish kinetics may prevent complete equilibration with Os-rich phases such as sulfides and alloys. Other possible explanations include the shielding of Os-rich phases in peridotite by silicates from reaction with partial melts of eclogite and the isolation of melt from peridotite by means of pyroxene-rich, Os-poor reaction zones along conduit walls. In the case of disequilibrium, the actual fraction of recycled component in OIB sources could be much lower than in equilibrium mixing models.